Secondhand homes: The multilayered influence of woodpeckers as ecosystem engineers. Issue 16 (22nd July 2021) - Hardin, Faith O.; Leivers, Samantha; Grace, Jacquelyn K.; Hancock, Zachary; Campbell, Tyler; Pierce, Brian; Morrison, Michael L.
Abstract: Ecosystem engineers alter, and can be influenced in turn by, the ecosystems they live in. Woodpeckers choose foraging and nesting sites based, in part, on food availability. Once abandoned, these cavities, particularly within areas of high forage, may be crucial to secondary cavity‐nesting birds otherwise limited by cavities formed through decay. Our study examined factors that influence the nesting success of primary cavity nesters and the subsequent impact on secondary cavity‐nesting birds. Using 5 years of point count data, we monitored the outcomes of cavity‐nesting birds in South Texas. We used logistic‐exposure models to predict daily survival rates based on cavity metrics and used woodpecker foraging trends and insect surveys to determine if nesting where woodpeckers actively forage benefits secondary cavity‐nesting birds. Both woodpeckers and secondary cavity nesters shared predictors of daily survival; nests were more successful in cavities with small openings in minimally decayed trees. All secondary cavity nesters had higher probabilities of success when nesting in an abandoned woodpecker cavity, opposed to ones formed by decay. Woodpeckers tended to forage in areas with higher‐than‐average levels of the insect orders Coleoptera, Hymenoptera, and Orthoptera, and secondary cavity nesters had higher rates of success when nesting in these areas. Our results suggest abandoned woodpecker cavities may be constructed in a way that directly benefit secondary cavity nesters. Additionally, we suggest an interplay between these ecosystem engineers, food availability, and secondary cavity nesters: Woodpeckers engineer superior nesting cavities in areas where food is more abundant, and the resultant cavities in areas of high forage may benefit local secondary cavity nesters. Our findings indicate that there is still much to be explored in the role of ecosystem engineers, and how they influence local communities on multiple trophic levels. Abstract : Woodpeckers leave behind nesting cavities that are crucial to secondary cavity‐nesting organisms. At a study site in southern Texas, USA, we evaluated how local secondary cavity‐nesting birds may be influenced by the placement and structure of abandoned Golden‐fronted woodpecker (Melanerpes aurifrons) cavities, in terms of both food resources and nesting success. We found that secondary cavity nesters had higher nest success in abandoned woodpecker cavities than in naturally occurring cavities, trends that correlated with both food resources in the area and the survival rates of the woodpecker chicks. Contrary to our previous understanding of woodpecker ecology, woodpeckers in this region chose dense, live trees in which to excavate nests as opposed to soft, decayed trees, potentially influenced by anti‐predator tactics and the extreme heat of the region.